Impact of Diabetes Type 1 in Children on Autonomic Modulation at Rest and in Response to the Active Orthostatic Test - Giacon, Thais Roque (PLoS One, 2016)
INTRODUCTION: Cardiovascular autonomic neuropathy is one of the most common complications of diabetes mellitus type 1 (DM1), of which one of the first subclinical manifestations is changes in heart rate variability (HRV). Thus, analysis of HRV associated with the autonomic active orthostatic test is important in this population. OBJECTIVES: To analyze the autonomic modulation responses induced by the implementation of the active orthostatic test, in children with DM1, and study the autonomic modulation by means of HRV indices. METHOD: Data of 35 children were analyzed, of both sexes, aged between 7 and 15 years, who were divided into two groups: Diabetic (n = 16) and Control (n = 19). The following variables were collected initially: weight, height, body fat percentage, heart rate, blood pressure and casual blood glucose. Subsequently, for analysis of autonomic modulation, the beat-to-beat heart rate was captured by a heart rate monitor in the supine position for 30 minutes and after 10 minutes standing during performance of the active orthostatic test. HRV indices were calculated in the time and frequency domains. For data analysis, covariance analysis was used to compare groups and ANOVA for repeated measures to compare the effects of the active orthostatic test. These data were adjusted for age, sex, ethnicity, body fat percentage and casual blood glucose, with a 5% significance level. RESULTS: The results suggested that diabetic children at rest present a decrease in SDNN (50.4 vs. 75.2), rMSSD (38.7 vs 57.6) and LF [ms(2)] (693.6 vs 1874.6). During the active orthostatic test the children in both groups demonstrated a reduction in SDNN, RMSSD and LF [ms(2)] compared to the resting position, and this response was less pronounced in the diabetic group. CONCLUSION: We conclude that regardless of age, sex, ethnicity, body fat percentage and casual blood glucose, performing the active orthostatic test promoted increased sympathetic modulation and reduced parasympathetic modulation in both groups, and this response was less pronounced in diabetic children, who presented reduced overall variability and parasympathetic modulation.